Ocular haemodynamics in patients with type 2 diabetes and coronary artery disease. Issue 5 (23rd January 2014) - Krasnicki, Pawel; Dmuchowska, Diana A; Proniewska-Skretek, Ewa; Dobrzycki, Slawomir; Mariak, Zofia
Abstract : Background/aims: To assess the relationship between ocular blood flow parameters and diabetic retinopathy and coronary artery disease in diabetic patients. Methods: 56 patients participated in the study. Colour Doppler imaging was used to assess the peak systolic and end-diastolic blood velocities as well as resistivity index in the ophthalmic, central retinal and posterior ciliary arteries. The diagnosis of coronary artery disease was based on the coronary angiogram. Results: As compared to controls, the peak systolic and end-diastolic blood velocities in all three evaluated vessels were significantly lower in the case of diabetic patients with coronary artery disease. Diabetic patients without coronary artery disease showed only decreased end-diastolic velocity values in the ophthalmic artery compared with the controls. Among diabetic patients, coronary artery disease was related to lower peak systolic and end-diastolic velocities in the central retinal artery and peak systolic velocities in the short posterior ciliary arteries. Diabetic retinopathy was significantly associated with a further decrease in end-diastolic blood velocity and an increase in resistivity index in the central retinal artery. Conclusions: (1) Flow disturbances within the ocular blood vessels of patients with type 2 diabetes were associated with atherogenic changes of coronary arteries. (2) In patients with type 2 diabetes and concomitant coronary artery disease, impaired blood flow within the ophthalmic and short posterior ciliary arteries was not related to diabetic retinopathy, but diabetic retinopathy was related to additional blood flow impairment within the central retinal artery.